What’s in a p? Reassessing best practices for conducting and reporting hypothesis-testing research - Meyer, Klaus E; van Witteloostuijn, Arjen; Beugelsdijk, Sjoerd (Journal of International Business Studies, 2017)
Social science research has recently been subject to considerable criticism regarding the validity and power of empirical tests published in leading journals, and business scholarship is no exception. Transparency and replicability of empirical findings are essential to build a cumulative body of scholarly knowledge. Yet current practices are under increased scrutiny to achieve these objectives. JIBS is therefore discussing and revising its editorial practices to enhance the validity of empirical research. In this editorial, we reflect on best practices with respect to conducting, reporting, and discussing the results of quantitative hypothesis-testing research, and we develop guidelines for authors to enhance the rigor of their empirical work. This will not only help readers to assess empirical evidence comprehensively, but also enable subsequent research to build a cumulative body of empirical knowledge.